Applications of Virtual Environments in Medicine - Riva, G. (Methods of Information in Medicine, 2003)
Objectives: This paper intends to investigate the role of virtual reality (VR) in medicine. In particular it outlines the current state of research and technology that is relevant to the development of effective virtual environments in medicine.Methods: After describing the two different visions of VR we can find in medicine – the presentation of virtual objects to all of the human senses in a way identical to their natural counterpart, and a new human-computer interaction paradigm in which users are active participants within a computer-generated three-dimensional virtual world – the paper presents some of the most interesting applications actually developed in the area. Finally, it discusses the clinical principles, technological devices and safety issues associated with the use of VR in medicine.Results: With more than 1,000 VR papers already indexed in Medline, VR is a reality health care. Even if the number of controlled studies is still limited, its merging with emerging technologies like Ambient Intelligence and wireless communication will further improve its diffusion.Conclusions: The possible impact of VR on health care could be even higher than the one offered by the new communication technologies like Internet. In fact, VR is at the same tima technology, a communication interface and an experience: a communication interface based on interactive 3D visualization, able to collect and integrate in single real-like experience different inputs and data sets. However, significant efforts are still required to move VR into commercial success and therefore routine clinical use.
Keywords: Virtual reality; medical education; surgical simulation; neuropsychological rehabilitation